Sexual Education Model in Indonesian Colleges: A Holistic Solution to Prevent Sexual Violence by Enhancing Bystander Role and Prosocial - Wahyuni, Sri; Nurbayani, Siti (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2025)
The college environment no longer solely concentrates on reviving efforts to treat and prevent sexual violence, but also promotes prevention as a preventive strategy through sexual education, which teaches students to maximize bystanders and cultivate prosocial attitudes. The research aims to examine the effectiveness of the sexual education (X) model at the Indonesian Educational University, the Bandung Institute of Technology, and Padjajaran University in enhancing the role of the behavior bystander (Y1) and encouraging the prosocial (Y2) attitude of students when faced with sexual violence. The research employed a quantitative approach, distributing the lift among 108 active students from the three universities. To ensure proportional representation, stratified random sampling divides students by university origin and then selects random samples from each layer of students who have received sexual education on campus. Additionally, we conducted interviews with the Prevention and Treatment Unit of Sexual Violence to gather information about the implemented model of sexual education. The research findings demonstrated the effectiveness of the university-implemented sexual education model, which enhanced bystander roles by 52.5% and prosocial attitudes by 51.9%. We regard the role of bystanders and prosocial attitudes in an incident of sexual violence as a holistic solution to sexual violence prevention, as they protect victims and prevent further sexual violence.